CONSUMER BEHAVIOUR TRENDS IN ON-CAMPUS RETAIL SPACES - Kshitij Srivastava, Pulkit Marwah, Sandeep Dongre (Lex localis-journal of local self-government, 2025)
This research paper studies the purchasing behaviours of consumers in on-campus retail spaces. The study, based on a survey of 61 respondents including students, staff, teachers, and visitors, found that the most important factors influencing purchasing decisions are product availability that is approximately 64% and quality convenience is approximately 50%. Other key factors include price and brand name, with students being specifically Inclined towards finding a pocket-friendly options. The research also highlights the role of modern technologies and growing consumer expectations. A significant finding is that about one-third of consumers regularly compare on-campus and off-campus prices, and a large majority (90.2%) prefer digital payment methods like UPI/QR codes. The study points a high level of satisfaction (100%) with the transformation of retail outlets, particularly concerning improvements in quality, ambience, and digital services following the COVID-19 pandemic.  Furthermore, the paper shows a surging interest in sustainability, with 83.3% of consumers supporting the idea of retail stores keeping eco-friendly products. The study concludes that on-campus retail spaces need to adapt to these changing consumer expectations by offering affordability, convenience, and sustainable options to enhance customer satisfaction and engagement